Finding the C4 sweet spot: cellular compartmentation of carbohydrate metabolism in C4 photosynthesis - Furbank, RT; Kelly, S (Society for Experimental Biology, 2021)
The two-cell type C4 photosynthetic pathway requires both anatomical and biochemical specialization to achieve a functional CO2-concentrating mechanism. While a great deal of research has been done on Kranz anatomy and cell-specific expression and activity of enzymes in the C4 pathway, less attention has been paid to partitioning of carbohydrate synthesis between the cell types of C4 leaves. As early as the 1970s it became apparent that, in the small number of species examined at the time, sucrose was predominantly synthesized in the mesophyll cells and starch in the bundle sheath cells. Here we discuss how this partitioning is achieved in C4 plants and explore whether this is a consequence of C4 metabolism or indeed a requirement for its evolution and efficient operation.